Teacher educators' learnings from change and growth in new educational contexts: Understanding identity, belonging and purpose. Issue 1 (1st January 2023) - Fitzgerald, Angela; Bradbury, Ondine Jayne
ABSTRACT: In an increasingly dynamic and ever-changing global context, mobility and employment choices has resulted in professional diversification and change. These changes have offered opportunity for two researchers to apply an analytic approach to their experiences. This collaborative self-study explores how being in a new educational context influenced and shaped the thinking of two teacher educators in relation to initial teacher education. Journal entries over a three-month period generated a set of three key themes – identity, belonging and purpose. Applying a critical friend methodological approach, these conversations helped the authors to further interrogate the data and make sense of their learnings. An important finding from the research is the power of the reflective process in truly engaging with the change and the significant personal growth that took place within each new context. The findings are pertinent others' experience change in educational context, such as pre-service teachers, which raises interesting questions and insights for those working with these cohorts and how best to prepare them for the dynamism of the profession.